Assessment of Referrals into the Soft Tissue Sarcoma Service: Evaluation of Imaging Early in the Pathway Process. (26th June 2012) - Rowbotham, Emma; Bhuva, Shaheel; Gupta, Harun; Robinson, Philip
Abstract : Purpose . To prospectively evaluate regional referrals into a soft tissue sarcoma service from outside the tertiary centre with local hospital imaging. Materials and Methods . Consecutive referrals were prospectively assessed for: patient demographics, source, referral date, date received by Multidisciplinary Team (MDT), lesion size, local radiology, MDT radiology and final diagnoses. Radiology diagnosis was categorised benign, indeterminate or malignant by consensus. Delays were defined as >10 days. Results . 112 patients were included with high correlation between local and MDT radiology categrorisation and histology (P = 0.54 and P = 0.49, resp.). There was only a trend for MDT radiology diagnosis to downgrade local imaging diagnosis (n = 15, P > 0.05 ). 48 cases (43%) had ultrasound and MRI at referral and 20 (18%) ultrasound only. 85% of cases were benign (lipoma most common), 15% malignant (sarcoma most common). Delay occurred in 34% of cases. Discussion . In comparison to previous series these results show a reduction in benign lesions, increased biopsy and malignancy rate for lesions referred to a tertiary centre when imaging is performed and reviewed by local radiologists. Advances in Knowledge . Imaging triage of soft tissue masses can decrease benign referral rates and increase the proportion of indeterminate and malignant lesions referred to specialist centres.